1999
DOI: 10.1111/j.1432-2277.1999.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral stenosis after kidney transplantation.

Abstract: Ureteral obstruction with impaired urine flow is the most common urological complication following renal transplantation. From December 3976 to December 1997,869 kidney grafts were performed by our kidney transplantation group, 96 from living related donors and 773 from cadaver donors (736 first grafts and 37 regrafts). A stricture of the ureter (SU) was observed in 27 cases with a follow-up ranging from 18 months to 18 years after the graft and 11 months to 11 years after the treatment of the SU. In six patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 20 publications
1
21
2
2
Order By: Relevance
“…Other risk factors include administering steroids, chronic rejection, and/or virus infection. 2,16,20,21 It has been observed that the features of presentation of US are associated with its causes. To perform prompt, effective treatment, we recommend the following 3 level classifications, based on the degree of US after a transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors include administering steroids, chronic rejection, and/or virus infection. 2,16,20,21 It has been observed that the features of presentation of US are associated with its causes. To perform prompt, effective treatment, we recommend the following 3 level classifications, based on the degree of US after a transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Ureteric obstruction occurring beyond the first postoperative month remains common (2e7.5%) [10,11] and mostly related to ureteral stenosis. In view of the risk of ischaemia to the distal ureter and subsequent risk of ureteric obstruction due to stenosis, we shortened the length of the tunnel.…”
Section: Methodsmentioning
confidence: 99%
“…There was no urine leakage occurred in this series. In single kidney transplant, the incidence of urological complications was reported from 3.6 to 5.8 % [12][13][14].…”
Section: Edkt (N=2) Udkt (N=7) Bdkt (N=1) Totalmentioning
confidence: 99%
“…One of the donors had high SCr (165 µmol/L) at the time of kidney procument. The incidence of DGF has been reported from 20% to 30% in dual kidney transplant [12,15]. The incidence of DGF may be attributed to longer CIT [16,17].…”
Section: Edkt (N=2) Udkt (N=7) Bdkt (N=1) Totalmentioning
confidence: 99%